Assessing the Possibilities of PCA as a Legal Avenue to Seek Compensation in the Aftermath of the Montara Oil Spill - Alexander (Center for Law and Responsible Business Studies, 2025)
The 2009 Montara Oil Spill, caused by the caused by the blowout of an offshore oil well operated by PTT Exploration and Production Public Company (PTTEP) Australasia (Ashmore Cartier) Proprietary Limited, had severe environmental and economic consequences for Indonesia. This article assesses the possible legal proceedings available to Indonesia for seeking compensation against Australia and PTTE AA in international tribunals, specifically the Permanent Court of Arbitration (PCA). That is to take account of liability with respect to relevant international law principles, including those pertaining to state responsibility and liability for transboundary harm as well as infringement of Indonesia's sovereign rights over its exclusive economic zone. The discussion will analyze the legal merits, jurisdictional aspects, and potential challenges associated with pursuing these legal proceedings in PCA.